Fabrication and characterization of large numerical aperture, high-resolution optical fiber bundles based on high-contrast pairs of soft glasses for fluorescence imaging - (:unkn) unknown (OPTICAL SOC AMER, 2019)
Fabrication and characterization of flexible optical fiber bundles (FBs) with in-house synthesized high-index and low-index thermally matched glasses are presented. The FBs composed of around 15000 single-core fibers with pixel sizes between 1.1 and 10 mu m are fabricated using the stack-and-draw technique from sets of thermally matched zirconium-silicate ZR3, borosilicate SK222, sodium-silicate K209, and F2 glasses. With high refractive index contrast pair of glasses ZR3/SK222 and K209/F2, FBs with numerical apertures (NAs) of 0.53 and 0.59 are obtained, respectively. Among the studied glass materials, ZR3, SK222, and K209 are in-house synthesized, while F2 is commercially acquired. Seven different FBs with varying pixel sizes and bundle diameters are characterized. Brightfield imaging of a micro-ruler and a Convallaria majalis sample and fluorescence imaging of a dye-stained paper tissue and a cirrhotic mice liver tissue are demonstrated using these FBs. demonstrating their good potential for microendoscopic imaging. Brightfield and fluorescence imaging performance of the studied FBs are compared. For both sets of glass compositions, good imaging performance is observed for FBs, with core diameter and core-to-core distance values larger than 1.6 mu m and 2.3 mu m, respectively. FBs fabricated with K209/F2 glass pairs revealed better performance in fluorescence imaging due to their higher NA of 0.59. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
Keywords: IN-VIVO; CONFOCAL MICROSCOPY; 2-PHOTON MICROSCOPE; SINGLE-FIBER; DEEP BRAIN; ENDOMICROSCOPY; ENDOSCOPY; PROBE; HEAD